Colorimetric determination of trace orthophosphate in water by using C18-functionalized silica coated magnetite - Vanpaseuth Phouthavong (Nature Portfolio, 2021)
Abstract In this study, we customized magnetic sorbents by functionalizing silica coated magnetite with octadecyl(C18)silane (Fe3O4@SiO2@C18). This sorbent was intended for the determination of trace orthophosphate (o-PO4 3−) in unpolluted freshwater samples. The o-PO4 3− was transformed to phosphomolybdenum blue (PMB), a known polyoxometalate ion. Then the PMB were coupled with cetyl trimethyl ammonium bromide (CTAB), cationic surfactant, in order to hydrophobically bound with the Fe3O4@SiO2@C18 particles through dispersive magnetic solid-phase extraction (d-MSPE) as part of sample preconcentration. The PMB–CTAB–magnetic particles are simply separated from the aqueous solution by the external magnet. The acidified ethanol 0.5 mL was used as PMB-CTAB eluent to produce an intense blue solution, which the absorbance was measured using a UV–Vis spectrophotometer at 800 nm. The proposed method (employing 2 mg of Fe3O4@SiO2@C18) yielded an enhancement factor of 32 with a linear range of 1.0–30.0 µg P L−1. Precision at 6.0 µg P L−1 and 25.0 µg P L−1 were 3.70 and 2.49% (RSD, n = 6) respectively. The lower detection limit of 0.3 µg P L−1 and quantification limit of 1.0 µg P L−1 allowed trace levels analysis of o-PO4 3− in samples. The reliability and accuracy of the proposed method were confirmed by using a certified reference material. Our method offers highly sensitive detection of o-PO4 3− with simple procedures that can be operated at room temperature and short analysis time.